Utilização e manejo do Buriti (Mauritia flexuosa L. f.) em comunidades indígenas na etnoregião do baixo São Marcos-RR - Sganzerla, Andressa Raquel Stroschein (2017)
Mauritia flexuosa L., known as buriti, is a palm tree of great cultural importance and subsistence for traditional communities in the state of Roraima, which have rich knowledge integrated with the use of plant species. The objective of this research was to characterize the management of buriti in the indigenous communities of Darora and Ilha - Indigenous Land of São Marcos - RR. In order to do so, the location of buriti areas of use and the survey on traditional knowledge and uses of buriti were carried out through interviews, workshops and observations. The data of structure and population dynamics were collected with the delimitation of 15 sample plots of 400 m² with the distribution of buritizeiros in ontogenetic classes: seedling, juvenile, immature and adults. From this, it observed was that the society-nature relations established with buriti directed are to subsistence, and there is no significant commercialization of products from them. The indigenous still have criteria of selection for buritis selection for straw and fruit extraction that depend on the purpose of the extraction and the stage in which the resource is found in nature. Regarding population structure and dynamics, the majority of the individuals were concentrated at the seedling and reproductive stages. Mortality was observed predominantly in individuals with DBH above 20 cm, and their plots with excess dry leaves on the soil, characterizing signs that these individuals were senescent. The data obtained suggest that the management of the Indians for this activity positively affects the production of new leaves, with a notable increase in the individuals with mark of withdrawals in previous moments. The Indians reported several problems about the scarcity of resources from the buritizais. The main one related was to the lack of straw enough to cover the roofs of the houses. Situation related to population growth and consequently the need for a greater amount of resource. The fire, culturally used for the preparation of sites for the construction of fields and for the renewal of native pastures for cattle raising, together with the grazing and trampling of cattle and horses, end up negatively pressing the regeneration of the buritizais by the low Number of young individuals in the populations. In view of the evidence of disturbance due to fire fighters and the presence of these animals near the burials, it concluded is that these anthropic disturbances may cause disturbances that hinder the development of the seedlings until the juvenile / adult stage. Consequently, Burials are seriously at risk of fading away if the problem of regeneration does not re-establish itself along with the mortality of adult individuals as a normal process in the buritizeiros cycle. In order to do so, it is considered that the construction of firebreaks and fences between areas of use for cattle and burials, the elaboration of a plan for the construction of sustainable management practices, as well as a record of the straw withdrawals can provide a better quality of life for the natives of the communities avoiding new damages in the environment.